2020
DOI: 10.1097/pec.0000000000002198
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Ultrasound to Assess Gastric Content in Pediatric Emergency Department Procedural Sedation Patients

Abstract: Objectives: There is debate regarding the timing of procedural sedation and analgesia (PSA) in relation to fasting status. Point-of-care ultrasound (POCUS) provides the ability to measure gastric content and is being used as a surrogate for aspiration risk in anesthesia. We sought to evaluate the gastric content of pediatric emergency department (PED) patients undergoing PSA using POCUS. Methods:We performed a prospective observational study using a convenience sample of pediatric patients undergoing PSA betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 82 publications
(231 reference statements)
0
18
0
2
Order By: Relevance
“…At the beginning of this study, there was no reference to guide sample size calculation to assess the presence of a sonographic empty stomach in PED patients with a scheduled revisit. We assumed an empty stomach ratio of 50% in patients presenting for a schedule revisit, based on prior studies of unscheduled PSA patients in the PED and nonelective pediatric surgery patients [19,20,22]. We calculated that enrollment of more than 93 patients from approximately 500 annual cases of PSA, would allow a 95% confidence interval for the proportion of empty stomach with a width of ±10%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…At the beginning of this study, there was no reference to guide sample size calculation to assess the presence of a sonographic empty stomach in PED patients with a scheduled revisit. We assumed an empty stomach ratio of 50% in patients presenting for a schedule revisit, based on prior studies of unscheduled PSA patients in the PED and nonelective pediatric surgery patients [19,20,22]. We calculated that enrollment of more than 93 patients from approximately 500 annual cases of PSA, would allow a 95% confidence interval for the proportion of empty stomach with a width of ±10%.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 82% of patients showed an empty stomach after a median NPO time of 7.5 hours for solid intake and 6 hours for clear liquid intake. This study included a population with lower age group, weight, and height but similar body mass index than in other studies [20][21][22]34]. The ROC analysis suggested the optimal cut-off of solid food NPO duration for gastric emptying was 6.5 hours when the patients had more than 2 hours of liquid fasting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It allows to personalize aspiration risk assessment and to tailor anesthetic management to the individual patient. [10][11][12][13][14] Lung POCUS has proven to be a valuable tool for the detection of pneumothorax, pleural effusion, consolidation and alveolar interstitial syndrome in the critical care setting, searching for signs like: Lung sliding (sliding of visceral and parietal pleura over one another with respiration), that may rule out pneumothorax, A lines (repeated parallel lines below pleura), suggesting that there is no parenchymal disease and B lines ( vertical lines) indicating fluid in the lungs or an interstitial syndrome. According to studies it seems to have comparable or even higher sensitivity and specificity than the chest x ray in diagnosing common lung pathologies as alveolar interstitial syndrome, consolidation, pleural effusion and pneumothorax.…”
mentioning
confidence: 99%